RANCANG BANGUN SIMULASI PENGENDALI LAMPU LALU LINTAS PADA PERSIMPANGAN DENGAN LIMA JALUR - Rahma Farah Ningrum; Rosidah Rosidah; Puji Puji (Jurnal Teknik, 2017)
The imbalance between the rapid increase in the number of motor vehicles in urban cities in Indonesia and the available transportation infrastructure, such as the capacity of the road,  has created more congestions or traffic jams . The congestions that  mostly occur at inter-sections or crossroads can cause several problems in terms of time delays, cost, health and environment issues due to air pollution. The traffic jams can be reduced by imposing the right traffic control.. One of the solutions to optimize the traffic condition at intersections is by controlling the traffic lights. Each traffic light at an intersection needs to have different set of green and red periods based on the current traffic condition. The purpose of this paper is to simulate the traffic condition at an intersection with 5  lines. The simulation can be used to display the results of the traffic light control possibilities on each line.  Keywords : traffic light, traffic control, simulation